1998
DOI: 10.1046/j.1525-1500.1998.cdoa43.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Tumor Response and Prognostic Factors of Survival during Lung Cancer Chemotherapy

Abstract: The aim of this study was (i) to determine predictive factors of a complete response to chemotherapy in small cell lung cancer (SCLC) and predictive factors of an objective response in non-small cell lung cancer (NSCLC) and (ii) to determine whether prognostic factors are different with regard to treatment response and survival. Ninety-nine patients with SCLC and two hundred and two patients with NSCLC received chemotherapy. The following variables were recorded prior to treatment: tumor, node, metastasis stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…Several studies suggest the tumor marker utility in prognosis, in both surgical and non-surgical NSCLC. Our results are similar to others that indicate a correlation among tumor markers, specially Cyfra 21.1, and tumor response in patients treated by chemotherapy [33][34][35].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies suggest the tumor marker utility in prognosis, in both surgical and non-surgical NSCLC. Our results are similar to others that indicate a correlation among tumor markers, specially Cyfra 21.1, and tumor response in patients treated by chemotherapy [33][34][35].…”
Section: Discussionsupporting
confidence: 92%
“…Serum LDH levels were independent determinants for OS in advanced NSCLC in some studies [2][3][4][5]15], but not in all studies [24,25]. Hespanhol et al [5] reported that the hazard ratio of abnormal serum LDH levels for death was 1.268 (95 % confidence interval 1.010-1.592) with adjusted p value of 0.04 in multivariate analysis, which was similar in our study.…”
Section: Discussionsupporting
confidence: 85%
“…They found that serum LDH levels, hemoglobin levels, calcium levels, metastatic extents, and chemotherapeutic agents were independent prognostic factors in good PS (PS 0-1) patients. In contrast, Ray et al [25] announced that high serum LDH levels were significant determinants of poor survival in only SCLC but not in NSCLC. The current study explored the clinical relationship between tumor and metastatic characteristics in advanced NSCLC in greater detail, and survival outcomes were analyzed alongside treatment-related factors.…”
Section: Discussionmentioning
confidence: 94%
“…Differences between the curves were tested for significance using one-sided log-rank statistics, and were estimated for noninferiority using the hazard ratio produced by the Cox regression model (Cox and Oakes, 1984). Furthermore, Cox regression models were used to evaluate treatment effects on survival, with adjustment for well-known prognostic factors: stage, PS, gender, weight loss, albumin and LDH (Albain et al, 1991;Espinosa et al, 1995;Paesmans et al, 1995;Ray et al, 1998). Response rates and toxicities were compared using the w 2 test.…”
Section: Discussionmentioning
confidence: 99%